KONTRIBUSI KELINCAHAN TERHADAP HASIL DRIBBLING SEPAKBOLA SISWA EKSTRAKURIKULER SEPAKBOLA SMAN 1 KAMPAR KEC. KAMPAR - Muhammad Yamin; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation of football exstracurricular in SMAN Kampar. Researcher found many student have deficiency of dribbling, visible when the student dribble imperfect, as the ball away from the feet, so that the ball easily captured opponent. It is influenced by physical conditions that agility. The purpose of this research is to see how much the contrubution of football dribbling result exstracurricular students of SMN 1 Kampar l. Population in this research was all students in football exstracurricular of SMAN 1 Kampar amount 22 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 22 people. Research instrument used dogging run test to agility and dribbling ball test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : Shows that there contribution between agility to ball dribblingl, which shows correlation rtab of significant α (0,05) = 0,433 mean rhitung(0,336) < rtab (0,433). This shows to get the good dribbling not only influenced by agility, but there are many more like speed and flexibility.Key word : Agility, Dribbling.